Plasma extracellular vesicles in meningioma patients following radiotherapy as liquid biopsy- a prospective explorative biomarker study (ARO 2023-05/AG-NRO-07) - Deng, Maximilian; Silva, Amanda Salviano da; Göller, Pauline C.; König, Laila; Schäfer, Henning; Maire, Cecile; Hommertgen, Adriane; Held, Thomas; Regnery, Sebastian; Eichkorn, Tanja; Stritzke, Florian; Bauer, Lukas; et al. (BMC cancer, 2024)
While surgical resection remains the primary treatment approach for symptomatic or growing meningiomas, radiotherapy represents an auspicious alternative in patients with meningiomas not safely amenable to surgery. Biopsies are often omitted in light of potential postoperative neurological deficits, resulting in a lack of histological grading and (molecular) risk stratification. In this prospective explorative biomarker study, extracellular vesicles in the bloodstream will be investigated in patients with macroscopic meningiomas to identify a biomarker for molecular risk stratification and disease monitoring.